Wolf–Hirschhorn syndrome candidate 1 facilitates alveolar macrophage pyroptosis in sepsis-induced acute lung injury through NEK7-mediated NLRP3 inflammasome activation. Issue 6 (August 2021) - Liu, Caixia; Cai, Benlong; Li, Dan; Yao, Yuan
Sepsis is a complex clinical syndrome with high incidence and mortality. Acute lung injury (ALI) is a common complication of sepsis. At present, there is no effective therapeutic strategy to treat ALI. The SET domain–containing histone methyltransferase Wolf–Hirschhorn syndrome candidate 1 (WHSC1) regulates cancer progression, while its role in sepsis-induced ALI remains unclear. Thus, this study aimed to study the effect of WHSC1 on sepsis-induced ALI and to explore the potential mechanism of action. In the study, LPS treatment induced lung injury. WHSC1 was highly expressed in LPS-induced ALI. Knockdown of WHSC1 attenuated LPS-induced ALI and pyroptosis in vivo . Besides, knockdown of WHSC1 attenuated LPS-induced alveolar macrophage pyroptosis in vitro . Furthermore, NIMA-related kinase-7 (NEK7) expression could be regulated by WHSC1, and NEK7 bound to NLRP3 in alveolar macrophages. Moreover, WHSC1 regulated alveolar macrophage pyroptosis through modulating NEK7-mediated NLRP3 inflammasome activation. In conclusion, WHSC1 was highly expressed in LPS-induced ALI. WHSC1 facilitated alveolar macrophage pyroptosis in sepsis-induced ALI through NEK7-mediated NLRP3 inflammasome activation. WHSC1 may be a valuable target for the therapy of sepsis-induced ALI.